Peran dan Kedudukan Perempuan Dalam Masyarakat Bugis Makassar dan Implikasinya Bagi Pemberitaan Injil - Dju, Nyoman Lisias F.; Wangania, Judith Debora L.; Evi (Jurnal Teologi Kontekstual Indonesia, 2025)
This study analyzes the role and position of women in the Makassar Bugis society and how the understanding of women's socio-cultural position can be an entry point for contextual gospel preaching. The results of the study show that Makassar Bugis women have a respectable position and a significant role in various aspects of life, including religious rituals, family decision-making, and the preservation of cultural values. This important role is rooted in traditional myths that are still firmly held today. The contextualization of the proclamation of the gospel can be done by utilizing women's strategic position in society, transforming their ritual role into ecclesiastical ministry, and developing an approach that respects local cultural values while affirming the truth of the Gospel.